Modern trends in Ghana music - Nketia, J. H. (International Library of African Music, 1957)
In Ghana two new musical traditions have emerged as a result of the forces of acculturation out of which Ghana herself has been born. The first which has developed gradually over the past sixty years or more is fairly well standardized and is popularly known by the English title of High Life, a title which reflects the early attitude of people to it as a new but somewhat insidious form of social music. Though based on gay rhythms of African foundation, it began from the inspiration of Western band music which was admired for its noisy splendour, and later the ballroom at which thoughtful Africans never looked favourably. These incorporated percussion and movement, and suggested a new line for creating a gay type of African music which would be markedly different from the lighter type of traditional music.
Keywords: African Music; Ghana